Spacerek Straomiejski . Walk in the Old Town of Warsaw - Munk, Andrzej (Poland, 1928)
A lyrical tale of a teenage music school student wandering through the Warsaw Old Town, finding beauty in the ordinary urban sounds. Based on the idea by composer Andrzej Markowski.